The Relationship Between Patient Satisfaction, Trust, and Health Worker’s Skill to Patient Loyalty in RSMM Papua - Deffina Widjanarko; Levin Septerian Gumulya; Siska Kristina Sari (Publikasi Indonesia, 2025)
Patient loyalty is critical for healthcare sustainability, especially in remote regions like Papua, where RSMM Hospital serves indigenous populations facing geographical and cultural barriers. Despite studies on loyalty drivers (e.g., satisfaction, trust), gaps persist in understanding how these factors operate in underserved, indigenous contexts. This study identifies determinants of patient loyalty at RSMM Papua, focusing on satisfaction, trust, and medical personnel skills, while addressing unique regional challenges. A cross-sectional quantitative design was employed, collecting data from 278 outpatients via validated questionnaires. SEM-PLS analysis tested relationships between latent variables (e.g., loyalty, satisfaction) using SmartPLS. All hypotheses were supported: medical personnel skills had the strongest effect on loyalty (B=0.482, p<0.001), followed by satisfaction (B=0.325) and trust (B=0.186). The model explained 66.3% of loyalty variance, with skills showing a strong effect size (f²=0.318). Results underscore the need for skills-based training and culturally adapted care in remote settings. Future research should explore longitudinal loyalty trends and digital health integration. This study provides actionable insights for policymakers and healthcare managers to enhance retention in marginalized communities.